On the determinants of euro area FDI to the United States: the knowledge- capital-Tobin's Q framework - Roberto A. De Santis; Robert Anderton; Alexander Hijzen (European Central Bank (ECB), 2004)
The long-run determinants of euro area FDI to the United States during the period 1980-2001 are explained by employing the Tobin's Q-model of investment. By using the fixed effects panel estimator, stock market developments in the euro area countries - including a measure adjusted for economic developments common to both the United States and the euro area - are found to influence euro area FDI to the United States. Moreover, the inclusion of the Tobin's Q enhances the traditional knowledge-capital framework specification. Overall, the empirical findings suggest that euro area patents (ownership advantage), various variables related to productivity in the United States (location advantage), the volume of bilateral telephone traffic to the United States relative to euro area GDP (ownership advantage), euro area stock market developments (Tobin's Q), and the real exchange rate are statistically significant determinants of euro area FDI to the United States.
Keywords: F21; F23; 330; euro area; Foreign Direct Investment; Multinational firms; Tobins Q